Effect of structural defects on the hydriding kinetics of nanocrystalline Pd thin films. (22nd June 2015) - Delmelle, Renaud; Amin-Ahmadi, Behnam; Sinnaeve, Marc; Idrissi, Hosni; Pardoen, Thomas; Schryvers, Dominique; Proost, Joris
Abstract: While the microstructure of a metal is well-known to affect its equilibrium hydrogen uptake and therefore the hydriding thermodynamics, microstructural effects on the hydriding kinetics are much less documented. Moreover, for thin film systems, such microstructural effects are difficult to separate from the internal stress effect, since most defects generate internal stresses. Such a decoupling has been achieved in this paper for nanocrystalline Pd thin film model systems through the use of a high-resolution, in-situ curvature measurement set-up during Pd deposition, annealing and hydriding. This set-up allowed producing Pd thin films with similar internal stress levels but significantly different microstructures. This was evidenced from detailed defect statistics obtained by transmission electron microscopy, which showed that the densities of grain boundaries, dislocations and twin boundaries have all been lowered by annealing. The same set-up was then used to study the hydriding equilibrium and kinetic behaviour of the resulting films at room temperature. A full quantitative analysis of their hydriding cycles showed that the rate constants of both the adsorption- and absorption-limited kinetic regimes were strongly affected by microstructure. Defect engineering was thereby shown to increase the rate constants for hydrogen adsorption and absorption in Pd by a factor 40 and 30, respectively. Highlights: We produced Pd films with similar internal stresses and different microstructures. Both rate constants for hydrogen adsorption and absorption were affected. The densities of grain boundaries, dislocations and twins were varied. Grain boundaries and dislocations generate irreversible H-traps in the Pd lattice.